Capacity development or new learning spaces through municipal international cooperation: Policy mobility at work?. (March 2015) - van Ewijk, Edith; Baud, Isa; Bontenbal, Marike; Hordijk, Michaela; van Lindert, Paul; Nijenhuis, Gerry; van Westen, Guus
The importance of strengthening local governments is widely recognised as local governments face new challenges against the backdrop of global decentralisation processes. Municipal International Cooperation (MIC) contributes strategically to such processes by peer-to-peer learning within existing local institutions, a development process that is both efficient and provides continuity. Empirically, the paper draws upon the findings of an evaluation of the Dutch support programme for MIC called LOGO South. The main conclusion is that partnerships between local authorities do strengthen local governments in the South; the unique approach of the LOGO South programme adds important spillover effects in mutual learning, resulting in both policy transfer and mobility. By creating multilevel governance networks, knowledge circulation was also strengthened. This paper contributes to the debate by showing that locally based, multilevel hybrid networks are strategic for governance processes.